Sustaining soil productivity 2 - Ahenkorah, Y.; Owusu-Bennoah, E. (Technical Centre for Agricultural and Rural Cooperation, 1996)
Sustaining soil productivity in intensive African agriculture is the proceedings of the seminar organized by CTA and held in Ghana in November 1993.